Clinical evaluation of women with PMB. Is it always necessary an endometrial biopsy to be performed? A review of the literature - Dimitraki, Marina; Tsikouras, Panagiotis; Bouchlariotou, Sophia; Dafopoulos, Alexandros; Liberis, Vasileios; Maroulis, Georgios; Teichmann, Alexander Tobias (Archives of gynecology and obstetrics, 2011)
Background Endometrial carcinoma is the most distressing cause of abnormal vaginal bleeding. The intention of clinical management in the case of postmenopausal bleeding is to achieve an accurate diagnosis without overinvestigation. Method We studied the available literature on the diagnostic evaluation of postmenopausal women with vaginal bleeding, accentuating the most important aspects on this topic: the accuracy of sonography and endometrial biopsy in predicting endometrial hyperplasia and endometrial carcinoma. Results The accuracy of the above tests in predicting endometrial hyperplasia and endometrial carcinoma is a subject of continuing debate. Μοreover, in the last decades, there has been an explosion of publications indicating that ultrasound may be useful in predicting endometrial pathology. Conclusion Since advanced endometrial carcinoma has been known to occur in cases without noticeable endometrial thickness on ultrasound, the clinician should beware of the diagnostic evaluation of postmenopausal women with vaginal bleeding.